EFFACT BLACK PEPPER, RED PEPPER, AND GINGER ON THE INTAKE OF Β-CAROTENE BY RAT INTESTINES - APPACHE, PROF.DOLON (International Journal of Multidisciplinary Research and Studies, 2021)
Given the widespread deficiency of A in populations hooked in to plant foods, it’s desirable to enhance the bioavailability of β-carotene. Specific dietary spices may alter the ultrastructure and permeability characteristics of the intestines. Few common spices were studied here for his or her possible influence on intestinal absorption of β-carotene by examining its uptake by the intestines from rats fed black pepper, red pepper, ginger, piperine, and capsaicin. Higher in vitro absorption of β-carotene within the intestines was evidenced altogether spice-fed animals. Dietary piperine and ginger increased the uptake of β-carotene by 147% and 98%, respectively. While the rise in absorption was 59% and 27% in black pepper and red pepper-fed animals, respectively, dietary capsaicin increased the identical by 50%. Thus, significantly enhanced intestinal uptake of β-carotene as a result of consumption of pungent spices was evidenced, which could form a food-based strategy to possibly reduce anti ophthalmic factor deficiency.